PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 003 TELUK BANO II - Farida, Asni; Noviana, Eddy; ', Zufriady (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research up on its low usufructs IPA results of class V in SDN 003 Teluk Bano II. Initially, of 22 students which reach KKM just 9 person (40,9%). Therefore researcher applies one kooperatif's learning model type Snowball Throwing . This learning model gets to coach student for over responsive accept order of others, and passes on that order to its friend in a body. This research constitute action research brazes that executed deep two cycles. Each cycle is performed in four meet times. Each cycle consisting four stages which is: (1 ) plannings, (2 ) Actions, (3 ) Watches, and (4 ) Reflections. Base to essay studying result, available result step-up studies IPA SD's student Country 003 Teluk Bano II. deep each its cycle. Average value on cycle i. to reach 72,25 and on cycle II. which is 85,75. klasikal's learned thoroughness on i. cycle which is 63,63%, cycle II. which is 95,45%. Learned yielding step-up IPA is followed even with teacher activity and student activity that increases. Skill learns on i. cycle to be gotten percentage average 80,67%, and on cycle II. acquired percentage average 92,04% includes in kualifikasi well. There is even, student activity individually on i. cycle to be gotten percentage average 74,99%, and on cycle II. acquired percentage average 88,88%. On cycles daily dry run i. student which complete 14 students whereas that don't complete 8 students, with klasikal's thoroughness (63,63%) (are not complete). Meanwhile on cycles daily dry run II. experience thoroughness step-up, complete student 21 person, meanwhile that don't complete 1, with klasikal's thoroughness (95,45%) (complete).Key word : Kooperatif's Learning Model Snowball Throwing , IPA Learned Result